Bone whistle modeling method based on robust scan point tracking - Khysru, Kuntharrgyal; Wei, Jianguo (Frontiers in Ecology and Evolution, 2023)
Several excavations at the Hemudu site in Zhejiang Province have led to the discovery of more than 100 pieces of bird bones that were likely used to create a kind of musical instrument.However, in contrast to the Jiahu bone flute, it is not clear for what the Hemudu bone whistle was used, although it was probably used for musical purposes. In this paper, the 7000-year-old Hemudu bone whistle is reproduced with 3D scanning and printing technology. Therefore, we propose a robust scan point detection and tracking method that includes three main stages.First, we conducted robust point detection and selection where noise and irrelevant points were removed. Then, we propose to track the key points and conduct 3D model optimization. With the above efforts, we obtained the 3D model of the bone whistle, and the audio of the bone whistle is replicated. The purpose of the bone whistles is inferred and evaluated through audio analyses.The experimental results show that the method is feasible.